PENGARUH ESG TERHADAP AGRESIVITAS PAJAK DENGAN PENGENDALIAN INTERNAL SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia Tahun 2021 - 2024) - Aulia Candra Pertiwi; Wahyu Meiranto (Diponegoro Journal of Accounting, 2026)
This study aims to examine the effect of Environmental, Social, and Governance (ESG) performance on tax aggressiveness, as well as the role of internal control as a moderating variable in energy sector companies listed on the Indonesia Stock Exchange (IDX). This study is grounded in agency theory, which explains that conflicts of interest and information asymmetry between principals and agents may influence corporate policies, including management’s tendency to engage in tax aggressiveness. This study uses secondary data sourced from company financial and annual reports and Bloomberg. The research sample consists of 17 companies, selected using the purposive sampling method with a period spanning 2021–2024. Data analysis employed panel data regression with 2 equation models, estimated using the Random Effect Model with Panel EGLS Cross-Section Weights in EViews 13, following prior stages of model selection testing and classical assumption tests, all of which were fully satisfied.            The results of the analysis indicate that ESG has no significant effect on tax aggressiveness, suggesting that the level of a company’s ESG score does not directly influence the degree of tax aggressiveness undertaken by the company. Furthermore, internal control is unable to moderate the relationship between ESG and tax aggressiveness, indicating that the company’s internal control system is not capable of altering the effect of ESG on tax aggressiveness, either by strengthening or weakening it.